Dispute or residing together in harmony? : bean cultivation and theft in rural Ethiopia - Gichamo, Tesfanesh Zekiwos (SLU/Dept. of Urban and Rural Development, 2011)

(untitled)
Previous studies in Beseku Ilala peasant association, South Central Ethiopia, have disclosed decreasing soil fertility in the area, a consequence of non-existent crop rotation practices, where a nitrogen-fixing legume, the faba bean (Vicia faba) is of particular interest. Widespread theft has resulted in the abandoning of bean cultivation. In order to solve this problem, the communities agreed to formulate by-laws, utilizing an existing local institution (Iddir) for the implementation. The people belonging to Iddir help members who mourn the death of a family member or a close relative. The aims of these by-laws were to punish the thieves and to urge and support farmers to start growing beans again. Most farmers had subsequently resumed bean cultivation, but in some areas farmers had refrained from growing the bean again.